Comparison between the use of one and two CT scans for attenuation correction of rest-stress myocardial perfusion SPECT with Tc-99m sestamibi - Narawong, Taratip; Wiyaporn, Kanyalak (The ASEAN Journal of Radiology, 2024)
Background: The standard protocol is to use separate computed tomography (CT) scans acquired during rest and stress for attenuation correction (AC) of myocardial perfusion (MP) single photon emission computed tomography (SPECT) imaging. Recently, there have been attempts to reduce the radiation dose by using one CT instead of two CTs. Objective: To compare between the use of one and two CTs for AC of rest-stress MP SPECT with Tc-99m sestamibi in quantification of MP and left ventricle (LV) function. Materials and Methods: Gated rest-stress MP SPECT images of 107 patients were reprocessed using 3 different AC methods: 1) rest CT for AC of rest SPECT and stress CT for AC of stress SPECT (2CT); 2) rest CT for AC of both rest and stress SPECT (1CT-rest); and 3) stress CT for AC of both rest and stress SPECT (1CT-stress). SPECT images obtained from 2CT and 1CT were used for quantification of MP values and LV function values. The values from 2CT and 1CT were compared. Results: The MP values of 2CT and 1CT showed a strong correlation (r≥0.712) and they did not differ significantly (p=0.106 to 0.931). In contrast, the LV function values of 2CT and 1CT exhibited a very strong correlation (r≥0.960), but they differ significantly (p=<0.001 to 0.004). Conclusions: The use of one and two CTs for AC in rest-stress MP SPECT with Tc-99m sestamibi can be interchanged for the quantification of MP, but not for the quantification of LV function.